2015
DOI: 10.1186/s12951-015-0109-1
|View full text |Cite
|
Sign up to set email alerts
|

One nanoprobe, two pathogens: gold nanoprobes multiplexing for point-of-care

Abstract: BackgroundGold nanoparticles have been widely employed for biosensing purposes with remarkable efficacy for DNA detection. Amongst the proposed systems, colorimetric strategies based on the remarkable optical properties have provided for simple yet effective sequence discrimination with potential for molecular diagnostics at point of need. These systems may also been used for parallel detection of several targets to provide additional information on diagnostics of pathogens.ResultsFor the first time, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Because the allele discrimination for the −13910C/T (dbSNP rs#: 4988235) is obtained by the AS-LAMP specificity, the Au-nanoprobe will only be positive if the correct fragment has been amplified since it will hybridize to the specific LAMP amplicon. The Au-nanoprobe is sequence specific, adding redundancy to the detection approach, increasing the specificity without additional equipment requirements [23] . This way, any unspecific amplification that might occur will not be score positive by the Au-nanoprobe detection.…”
Section: Resultsmentioning
confidence: 99%
“…Because the allele discrimination for the −13910C/T (dbSNP rs#: 4988235) is obtained by the AS-LAMP specificity, the Au-nanoprobe will only be positive if the correct fragment has been amplified since it will hybridize to the specific LAMP amplicon. The Au-nanoprobe is sequence specific, adding redundancy to the detection approach, increasing the specificity without additional equipment requirements [23] . This way, any unspecific amplification that might occur will not be score positive by the Au-nanoprobe detection.…”
Section: Resultsmentioning
confidence: 99%
“…For example, AuNPs have been combined with inkjet-printed, dye-sensitised TiO 2 photodetectors as a means of detection to generate colorimetric biosensors with a limit of detection (LOD) of 1 nm DNA [ 27 ]. Recently, this method was further enhanced to simultaneously detect two different pathogens in one reaction [ 28 ]. Duan et al recently employed immobilised HBV and hepatitis C virus (HCV) antigens, staphylococcal protein A (SPA)-labelled AuNPs and a silver staining step to increase the optical signal to simultaneously detect antibodies to HBV and HCV antigens [ 29 ].…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…Veigas et al (62) showed for the first time that by functionalizing a single Au-nanoprobe with multiple sequences, in the presence or absence of two pathogens could be determined in a single test. The selected targets were the conserved region of the Mycobacterium tuberculosis rpoB gene and Plasmodium 18S ribosomal RNA (18S rRNA).…”
Section: Micro/nanotechnology Diagnostic Innovationsmentioning
confidence: 99%